GABAergic Mechanisms Contributing to Categorical Amygdala Responses to Chemosensory Signals - Westberry, Jenne M. (Neuroscience, 2016)
Chemosensory stimuli from conspecific and heterospecific animals, elicit categorically different immediate-early gene response-patterns in medial amygdala in male hamsters and mice. We previously showed that conspecific signals activate posterior (MeP) as well as anterior medial amygdala (MeA), and especially relevant heterospecific signals such as chemosensory stimuli from potential predators also activate MeP in mice. Other heterospecific chemosignals activate MeA, but not MeP. Here we show that male hamster amygdala responds significantly differentially to different conspecific signals, by activating different proportions of cells of different phenotype, possibly leading to differential activation of downstream circuits. Heterospecific signals that fail to activate MeP do activate GABA-immunoreactive cells in the adjacent caudal main intercalated nucleus (mICNc) and elicit selective suppression of MeP cells bearing GABA-Receptors, suggesting GABA inhibition in MeP by GABAergic cells in mICNc. Overall, work presented here suggests that medial amygdala may discriminate between important conspecific social signals, distinguish them from the social signals of other species and convey that information to brain circuits eliciting appropriate social behavior.